The benefit of co-trimoxazole treatment in the management of acute watery diarrhea caused by invasive bacterial infection - Bobby Setiadi Dharmawan; Agus Firmansyah; Imral Chair (Paediatrica Indonesiana, 2007)
Background World Health Organization (WHO) states thatantimicrobials are reliably helpful only for children with bloodydiarrhea (probable shigellosis), suspected cholera with severedehydration, and symptomatic infection caused by Giardia lamblia.The benefit of antimicrobial treatment in management of acutewatery diarrhea caused by invasive bacterial infection is still debated.Objective To prove the benefit of co-trimoxazole treatment inthe management of acute watery diarrhea caused by invasivebacterial infection in patients age 2–24 months.Methods This was a randomized, double blind clinical trialinvolving infants and children aged 2–24 months with acutewatery diarrhea caused by invasive bacterial infection withoutco-morbidity or complications. Invasive bacterial infection wasdefined by fecal leukocytes greater than ten cells (+2) per highpower field on stool. Subjects were assigned to receive either co-trimoxazole or placebo. The duration and frequency of diarrheabetween two groups were compared.Result Of 70 patients (co-trimoxazole, n=35; placebo, n=35),42 (60%) were children aged 12–24 months, of whom 61% wereundernourished. Males were affected 1.2 times as much as females.The clinical manifestations were mild-moderate dehydration(64%), mucus in the stool (100%), fever (24%), vomiting (10%),fever with vomiting (56%) and lactose malabsorption (53%).Duration of diarrhea in placebo group (mean 117.0 [SD 28.1]hours) was not significantly different (P=0.43) compared to thatin co-trimoxazole group (mean 122.5 [SD 30.1] hours). Frequencyof diarrhea per day in placebo group (mean 5.23 [SD 1.48] times)was not significantly different either (P=0.37) compared to thatin co-trimoxazole group (mean 5.64 [SD 2.20] times).Conclusion It is concluded that co-trimoxazole therapy providesno benefit to patients with acute watery diarrhea caused byinvasive bacterial infection. This disorder seems to be self-limited.